Competencias profesionales de los técnicos de banano del Ministerio de Agricultura de la Provincia de Los Ríos. - Cabezas Contreras, Lisbeth Alejandra (2020)
The present work was carried out with the purpose of analyzing the professional competence of the banana technicians of the Ministry of Agriculture of the Province of Los Ríos, in order to determine if the capacity and abilities are the main causes of the problems that are affecting the competitiveness in the internal and external activities that are executed in said entity, since the main inconvenience that appears in this institution is the nonexistence of a training plan that helps with the progress of its collaborators and of the same. Taking into account that this establishment is committed to improving the development of rural areas through events and technical advice that helps improve the knowledge of agricultural producers and in this way, they can offer a quality product and achieve participation commercial in national and international markets.